Vers la société de l’information - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Internet. Une chance pour l’Afrique Par Jacques Bonjawo. Karthala, Paris, 2002. 208 pages, ISBN 2-84586-259-8 18 Les Éditions Karthala 22-24, boulevard Arago 75013 Paris France Fax: + 33 1 45 35 27 05 E-mail: karthala@wanadoo.fr Site Web: www.karthala